The effect of talent management on organizational identification: Field study on the Office of Innovation Support, Technology Transfer and Marketing at Al-Azhar University (TAICO) - Arab Republic of Egypt - Sewify, Abeer Mokhtar (Journal of Economic, Administrative and Legal Sciences, 2021)
The current research aims to examine the impact of talent management on the organizational identification. The research was conducted in the Office of Innovation Support, Transfer and Marketing of Technology at Al-Azhar University. The importance of the research is derived from the need of investigated organization to apply effective talent management which maximize benefiting from talents. The research problem was represented in the following inquiry: Does talent management have an impact on organizational identification of members and coordinators of the Office of Innovation, Technology Transfer and Marketing (TAICO) at Al-Azhar University? The research attempted to test the validity of the following hypotheses: There is a high level of practicing talent management in the investigated organization, -There is a high level of practicing organizational identification in the investigated organization. -Talent management has a significant positive impact on organizational identification. The number of members and coordinators of the TAICO office reached 37 people, yet 32 of them were listed at 86%. The research relied on the Analytical descriptive method. Some statistical methods were used, including the Pearson correlation coefficient and the T-test, as well as the simple regression test to determine the correlation and impact relationships. Moreover, results showed that talent management obtained a low estimation with mean of 2.36, also, the mean of organizational identification was 2.40. Results indicated that there was a significant effect of talent management on organizational identification, as T value reached 9.628, which was significant at 0.01 level. The research recommended the necessity of adopting effective talent management strategies to discover talented people, observe their development and direct them in the right direction, and also conducting a periodic evaluation that shows the extent of the development of those talents and finding common values and goals between the members and the TAICO office, in a way that contributes to enhancing organizational identification.
Keywords: talent management; Organizational Identification; Office of Innovation Support; TAICO; Technology Transfer and Marketing at Al-Azhar University (TAICO)